COVID -19- Infodemic overtaking Pandemic? Time to disseminate facts over fear - Kulkarni , Praveen; Prabhu, Sudhir; Kumar, Sunil; Ramraj, Balaji (Indian Journal of Community Health, 2020)
Coronavirus (COVID-19) is a humanitarian emergency. World Health Organization (WHO) and National Governments are making their best efforts to prevent the spread of disease. But a global epidemic of misinformation which is rapidly spreading through social media platforms and other outlets is posing serious problem to the public health interventions. This rapid spread of all sorts of information pertaining to the epidemic which makes its solution difficult is termed as infodemic. Infodemic creates fear, confusion and stigmatization among people and makes them more vulnerable to practice the measures which are not evidence based and scientifically sound. Hence there is an urgent need to identify the source of misinformation and prevent them from further spreading. WHO and the government of India have taken several steps in controlling this problem but there is a need for active involvement of social media companies, professional bodies, health care providers and general public in identification of misinformation and combating its spread.